2014
DOI: 10.1117/1.oe.53.1.014106
|View full text |Cite
|
Sign up to set email alerts
|

Studying the effect of zeolite inclusion in aluminum alloy on measurement of its surface hardness using laser-induced breakdown spectroscopy technique

Abstract: Laser-induced breakdown spectroscopy (LIBS) has been used to study the surface hardness of special aluminum alloys containing zeolite. The aluminum alloy has acquired pronounced changes in its metallurgical properties due to the zeolite inclusion. The surface hardness of the samples under investigation is determined by measuring the spectral intensity ratios of the ionic to atomic spectral lines in the LIBS spectra of samples having different surface hardness values that have been conventionally measured befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…This result confirms that the ratio of the ionic to atomic Cr II/Cr I spectral lines' emission intensity could be a valuable measurement tool for the surface hardness. This relationship with the mechanical hardness has been established in case of iron-based materials [30], cast iron samples [31] and aluminum alloy containing zeolite [32].…”
Section: Libs-hardness Methodsmentioning
confidence: 84%
“…This result confirms that the ratio of the ionic to atomic Cr II/Cr I spectral lines' emission intensity could be a valuable measurement tool for the surface hardness. This relationship with the mechanical hardness has been established in case of iron-based materials [30], cast iron samples [31] and aluminum alloy containing zeolite [32].…”
Section: Libs-hardness Methodsmentioning
confidence: 84%
“…We measured 2θ from 30° to 90°, but significant difference in the peak analysis, in terms of annealing, was not found except in 2θ = 82.5°. From the literature [ 34 , 35 , 36 ], we found that this value of 2θ indicates the presence of aluminum silicate. That is why we narrowed down the whole XRD waveform into around 80 degree.…”
Section: Resultsmentioning
confidence: 99%
“…The point of intersection of the second derivative of the C–V curve with the Vg-axis is zero, which is called the inflection point, as well as the value of flat-band voltage [ 33 ]. Most researchers have stated that V FB shifts owing to ion diffusion at the annealing temperature [ 21 , 22 , 23 , 24 ]; this results in an additional aluminum silicate layer at the interface of the Si substrate and oxide layer, as presented by the X-ray diffraction (XRD) data in Figure 2 b (each sample exhibits peaks at 82.5°) [ 34 ]. For the XRD measurements, the annealing time was set to 5 min, and the temperatures were 300, 400, and 500 °C.…”
Section: Resultsmentioning
confidence: 99%
“…A typical LIBS experimental setup, described in details elsewhere [20], has been used in the present work. Briefly, the used laser was a Q-switched Nd: YAG laser (Brilliant Eazy, Quantel, France) producing 5 ns laser pulses each of 150 mJ energy at 1064 nm wavelength and 1 Hz repetition rate.…”
Section: Methodsmentioning
confidence: 99%